ANALYSIS OF THE FOREIGN GOVERNMENT AND CORPORATE PROCUREMENT MANAGEMENT EXPERIENCE - Vladimir Vladimirovich Savchenko (Модернизация, инновация, развитие, 2016)
This article presents a synthesis of the experience of foreign government and corporate procurement management. Set out key aspects of the organization of procurement for government and corporate needs, disclosed issues of centralization and decentralization of procurement, as well as given clarifi cation of the concept of "procurement management system" and structured the main elements that make up this system. The purpose / goal. The purpose of the work is to study the nature and characteristics of the functioning of government and corporate experience in procurement management, identifying problems and prospects of its development. Methodology. To perform this work were used legal, comparative and statistical analysis methods. Results. As part of the presentation of the present article the author has examined the nature, objectives and stages of public and corporate procurement management.